The Effect of the CORE Learning Model on Students' Mathematical Connection Ability in terms of Their Preliminary Knowledge in Mathematics - Rahmadhani, Calista; Syamsuri, Syamsuri; Santosa, Cecep Anwar Hadi Firdos (International Journal of STEM Education for Sustainability, 2024)
This study aimed to explain the effect of CORE (connecting, organizing, reflecting, and expanding) learning with a metacognitive approach on students’ mathematical connections in terms of preliminary knowledge in mathematics (PKM). The method in this study used a quasi-experimental with a posttest-only control group design. The population in this study consisted of all students at one of junior high schools in Indonesia. The sample was divided into two types: class VIII A as an experimental class with 13 students and class VIII B as a control class with 14 students. The instruments used in this study were essay tests to measure students' mathematical connection abilities and interview guidelines. Data analysis was performed by analysis of covariance. This study's results indicate a linear relationship between PKM and mathematical connection abilities. There is an effect of PKM on students' mathematical connection abilities. There is a simultaneous effect between PKM and the learning model; in other words, there is an interaction between PKM and the learning model. The CORE learning model with a metacognitive approach is more suitable for high PKM, and the scientific model is more suitable for low PKM.